2020
DOI: 10.1515/eng-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nozzle hole diameter of 3D printing on porosity and tensile strength parts using polylactic acid material

Abstract: Nozzle hole diameter of 3D printer (3DP) can be varied to obtain required product quality as well as to reduce manufacturing times. The use of larger diameter may accelerate manufacturing times of products, yet the product quality, including the mechanical properties, still needs to be investigated profoundly. The purpose of this work is to investigate experimentally the effect of nozzle hole diameter of 3DP to the surface quality, accuracy, and the strength of the product. The specimens were manufactured by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 25 publications
2
28
0
4
Order By: Relevance
“…The use of a nozzle with a large hole diameter accelerates the part production time [ 98 ]. It has also been reported that increasing the nozzle diameter increases the part quality and mechanical properties in FDM 3D printing [ 99 ]. The other important parameter is the ambient temperature which causes part warpage.…”
Section: Printing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a nozzle with a large hole diameter accelerates the part production time [ 98 ]. It has also been reported that increasing the nozzle diameter increases the part quality and mechanical properties in FDM 3D printing [ 99 ]. The other important parameter is the ambient temperature which causes part warpage.…”
Section: Printing Processmentioning
confidence: 99%
“…Nozzle temperature is the temperature at which the material is melted and extruded from the nozzle. It has a high influence on the mechanical properties and microstructure of the 3D printed parts [ 99 ]. For instance, the increase in relative density (from 89.9% to 92.8% for PEEK) with the increase in nozzle temperature from 370 °C to 390 °C is reported [ 103 ].…”
Section: Printing Processmentioning
confidence: 99%
“…This was explained, by the authors, by the gravitational force that helps to spread the melted plastic and it is more efficient for large nozzle diameters. Triyono et al (2020) [79] investigated the effect of nozzle diameter on the ultimate tensile stress (UTS) of 3D-printed PLA parts. The nozzle diameters used in this study varied from 0.3 to 0.6 mm.…”
Section: Effect Of the Nozzle Diametermentioning
confidence: 99%
“…Triyono et al (2020) [ 79 ] investigated the effect of nozzle diameter on the ultimate tensile stress (UTS) of 3D-printed PLA parts. The nozzle diameters used in this study varied from 0.3 to 0.6 mm.…”
Section: Influence Of Process Parameters On the Strength Of Fdm Partsmentioning
confidence: 99%
“…Penelitian terhadap filamen PLA dengan pengaturan bed temperature 60°C, nozzle temperature 200°C, dan printing speed 80 mm/s. Type infill bentukl line dengan densitas 100% menunjukkan bahwa semakin besar nozzle yang digunakan memberikan pengaruh terhadap kuat tarik, tetapi tidak meningkat signifikan atau tidak meningkat secara linear [14]. Tujuh variasi diameter nozzle, 0,2mm, 0,3mm, 0,4mm, 0,5mm, 0,6mm 0,8mm, dan 1mm telah digunakan untuk mencetak spesimen uji tarik standar PN-EN ISO 527:1998 menunjukkan bahwa diameter nozzle 0,5mm menghasilkan kuat tarik tertinggi yaitu 1,93 kN [15].…”
unclassified